Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1248/bpb.b13-00553
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Protamine Uptake by Opossum Kidney Epithelial Cells

Abstract: Protamine, a mixture of polypeptides that is rich in arginine, has been used clinically as an antidote to heparin overdoses and a complexing agent in a long-acting insulin preparation. When protamine is administered intravenously, its abundant accumulation in the kidneys has been reported. However, the renal uptake mechanism for protamine is not clear. In this study, we examined the transport mechanism for protamine in opossum kidney (OK) cells, a suitable in vitro model for renal proximal tubular epithelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Data from recent studies showed that the cationic proteins and peptides, inhibit the uptake of a nephrotoxic drug, gentamicin, which is highly accumulated in the kidneys. [ 15 16 ] Some authors report that L-arginine might have protected tubular function simply by decreasing gentamicin reabsorption in the proximal tubules. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Data from recent studies showed that the cationic proteins and peptides, inhibit the uptake of a nephrotoxic drug, gentamicin, which is highly accumulated in the kidneys. [ 15 16 ] Some authors report that L-arginine might have protected tubular function simply by decreasing gentamicin reabsorption in the proximal tubules. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Expression of PEPT2 Protein Detected by Western Blotting and Confocal Laser Scanning Microscopy The crude membrane fraction was prepared from H441 cells as described previously. 11) The expression of PEPT2 protein in the crude membrane fraction was examined by Western blotting, using rabbit polyclonal anti-PEPT2 antibodies (NBP1-59626; 1 : 1000 dilution) (Novus Biologicals, LLC, Centennial, CO, U.S.A.) as the primary antibody and peroxidase-labelled affinity purified antibodies to rabbit immunoglobulin G (IgG) (H + L) (1 : 2000 dilution) as the secondary antibody, as described previously. 5) β-Actin was detected with mouse monoclonal anti-β-actin antibodies (A2228; 1 : 2000 dilution) (Merck KGaA, Darmstadt, Germany) and used as a loading control.…”
Section: Methodsmentioning
confidence: 99%
“…87 PTDs cross membranes through protein transduction, facilitating the transport of fused materials across cellular membranes. 88 PTDs can be linked covalently to onaBoNT-A to facilitate their entry into any cell type independent of receptors and transporters. TAT peptide is a PTD derived from human immunodeficiency virus (HIV), which was successfully employed for the uptake of peptide nucleic acids, conjugated with TAT peptide, into rat bladders.…”
Section: Latest Developmentsmentioning
confidence: 99%